Pengembangan Sistem Steganografi Berbasis Web Menggunakan Metode Least Significant Bit (LSB) - Aiman Fawwaz; Alifmulya Rahman; Muhammad Akbar; Rahmad Hidayah Damanik (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Concealing digital information within images has become increasingly important with the growing demand for data security in the digital era. This research develops a web-based steganography system using the Least Significant Bit (LSB) method to hide secret messages within digital images. The system is designed with a user-friendly web interface featuring two main functions: (1)